Available Methods for Benefit-risk Assessment: Lessons for Inflammatory Bowel Disease Drugs. (11th August 2022) - Caron, Bénédicte; D'Amico, Ferdinando; Jairath, Vipul; Netter, Patrick; Danese, Silvio; Peyrin-Biroulet, Laurent
Abstract: Background and Aims: Medical treatment for inflammatory bowel disease has advanced significantly over the two past decades. The advent of biologics and small molecules has revolutionised outcomes for patients with inflammatory bowel disease. Knowledge of drug pharmacology, indications, and adverse events is essential to ensure the best clinical care while minimising toxicity. Our aim was to review the literature on current methods of benefit-risk assessment, and consider their practical applicability to inflammatory bowel disease. Methods: A literature search was conducted to investigate studies documenting benefit-risk assessment. Results: Several structured frameworks and quantitative methodologies have been developed to evaluate benefit-risk profiles of drugs in a more comprehensive and consistent framework. Quantitative methods integrate benefit and risk outcome measures or incorporate preference weights for benefit and risk criteria into the evaluation. Incorporation of preference weights from patients is an essential aspect of quantitative benefit-risk assessment. Benefit-risk assessment is still evolving in inflammatory bowel disease. Conclusions: The risks and benefits of each medical therapy must be discussed with the patient and a shared decision-making process is recommended. Future initiatives should be developed to perform a benefit-risk assessment considering the characteristics of inflammatory bowel disease drugs.